Efficacy and safety of propranolol in infants with heart failure due to moderate-to-large ventricular septal defect (VSD-PHF study) - A prospective randomized trial - Sivasubramanian Ramakrishnan; Nirmal Ghati; Ramandeep Singh Ahuja; Kinjal Niranjan Bhatt; Hem Chandra Sati; Anita Saxena; Shyam Sunder Kothari (Wolters Kluwer Medknow Publications, 2021)
Aims : The utility of beta-blocker therapy in infants with heart failure (HF) due to significant left-to-right shunt lesions is not known. The study aimed to assess the efficacy and safety of propranolol in infants with HF due to moderate-to-large ventricular septal defect (VSD). Methods : The prospective randomized trial included 80 infants with HF and moderate-to-large VSD, randomly allocated to receive either conventional therapy alone (n = 40) or propranolol plus conventional therapy (n = 40). The primary endpoint was a composite of all-cause mortality, hospitalization for HF and/or chest infection, and referral for surgery. The secondary clinical outcomes were the individual components of the composite endpoint. In addition, the patients were followed up to detect safety outcomes, for example, bronchospasm, bradyarrhythmia, and worsening HF symptoms. Results : The addition of propranolol therapy to the conventional medications did not result in significant improvement in the primary composite endpoint (32.50% vs. 52.50%; P = 0.07). There was a trend toward improvement, but the study is underpowered for this important question. However, propranolol therapy significantly decreased the risk of hospitalization (12.50% vs. 32.50%; P = 0.03) and worsening of Ross HF class (5.41% vs. 28.21%; P = 0.01) as compared to conventional therapy (estimated number needed to treat = 5). Propranolol did not result in any significant safety concerns in these infants except bronchospasm in an infant. Conclusions : Propranolol therapy in infants with significant left-to-right shunt may prevent worsening in HF symptoms and hospitalization and is well tolerated. However, it does not reduce mortality or need for surgery.